1998
DOI: 10.1128/mcb.18.11.6245
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Regulation of Schwann Cell Proliferation by Heregulin and Forskolin

Abstract: A peptide corresponding to the epidermal growth factor homology domain of ␤-heregulin stimulated autophosphorylation of the heregulin receptors erbB2 and erbB3 in Schwann cells and activation of the mitogen-activated protein (MAP) kinases ERK1 and ERK2. Heregulin-dependent activation of PAK65, a component of the stress-activated signaling pathway, ribosomal S6 kinase, and a cyclic AMP (cAMP) response element binding protein (CREB) kinase, identified as p95 RSK2, was also observed. Receptor phosphorylation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 38 publications
(67 reference statements)
6
90
1
1
Order By: Relevance
“…Increasing cAMP alone, in the absence of serum or exogenous growth factors, does not increase proliferation but induces markers of differentiation, e.g., P0 (Morgan et al, 1991). However, when cAMP is elevated in concert with exposure to serum or growth factors, such as neuregulin, then a synergistic effect is seen and there is robust cell proliferation (Lemke and Brockes, 1984;Stewart et al, 1991;Kim et al, 1997;Rahmatullah et al, 1998;Monje et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing cAMP alone, in the absence of serum or exogenous growth factors, does not increase proliferation but induces markers of differentiation, e.g., P0 (Morgan et al, 1991). However, when cAMP is elevated in concert with exposure to serum or growth factors, such as neuregulin, then a synergistic effect is seen and there is robust cell proliferation (Lemke and Brockes, 1984;Stewart et al, 1991;Kim et al, 1997;Rahmatullah et al, 1998;Monje et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…monkey kidney) were grown at 37°C in DMEM͞2.5% (vol͞vol) FCS. T. cruzi trypomastigotes, Silvio strain, were maintained in Vero cell cultures (16). T. cruzi epimastigotes were grown in acellular medium at 26°C (18).…”
Section: Methodsmentioning
confidence: 99%
“…Like primary cultures of rat Schwann cells (11,16), immortalized Schwann cells, when grown in serum-free medium, underwent apoptosis in a time-dependent manner, such that about 50% of the cells exhibited apoptosis by 72 hr (Fig. 1A Left and Fig.…”
Section: T Cruzi Invasion Blocks Apoptosis Of Schwann Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have hypothesized that inappropriate signaling by proteins in the neuregulin-1 (NRG-1) family of growth and differentiation factors contributes to the pathogenesis of peripheral nerve sheath tumors. NRG-1 proteins stimulate the proliferation, survival and migration of developing Schwann cells (Dong et al, 1995;Morrissey et al, 1995;Rahmatullah et al, 1998), and activating mutations of the NRG-1 receptor subunit erbB2 promote MPNST formation in rodents exposed to the mutagen N-ethyl-N-nitrosourea (EtNU) in utero (Bargmann et al, 1986;Hudziak et al, 1987;Bargmann and Weinberg, 1988;Weiner et al, 1989;Di Marco et al, 1990;Nikitin et al, 1991;Sherman et al, 1999). We have found that JS1 cells, a rat cell line derived from an EtNU-induced MPNST, lack this erbB2 mutation and express erbB2 in combination with the NRG-1 receptor subunit erbB3 and multiple NRG-1 isoforms.…”
Section: Introductionmentioning
confidence: 99%